An hp Adaptive Uniaxial Perfectly Matched Layer Method for Helmholtz Scattering Problems (Communications in Computational Physics, 2018)
We propose an adaptive strategy for solving high frequency Helmholtz scattering problems. The method is based on the uniaxial PML method to truncate the scattering problem which is defined in the unbounded domain into the bounded domain.The parameters in the uniaxial PML method are determined by sharp a posteriori error estimates developed by Chen and Wu [8]. An hp-adaptive finite element strategyis proposed to solve the uniaxial PML equation. Numerical experiments are includedwhich indicate the desirable exponential decay property of the error.